Effect of Supplementation of Branched Chain Fatty Acid on Colony of Ruminal Bacteria and Cell of Protozoa - Suryapratama, W; Suhartati, FM (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
A study was conducted to evaluate the potential of branched-chain volatile fatty acids (isobutyric, α-methylbutyric and β-methylbutiric) that supplemented into the diet on the colony of ruminal bacteria and the cell of protozoa population. Five progeny Friesian Holstein males with initial weight 348±29 kg were used in a 5x5 Latin square design (30-d periods). The basal diet composed of 55% forage and 45% concentrate containing 10.5 MJ ME/kg and 15% crude protein (CP). There were five dietary treatments where A: basal diet, B: A+139 mg urea/kg W0.75, C: B+28 mg CaSO4/kg W0.75, D: C+0.05 mM isobutyric acid+0.05 mM β-methylbutyric acid, and E: D+0.05 mM α-methylbutyric acid. Rearing period was 30 days, consists of feed adaptation period 20 days, then growth observation was done within the last 10 days. Collection of ruminal fluid was done within the last day of observation period, and took 3-4 h after the feeding. The results showed that supplementation branched chain volatile fatty acids did not significant affect on the number of colonies of bacteria and protozoa population, but the significant effect (P<0.05) on the concentration of branched chain volatile fatty acids in the rumen fluid. The supplementation of α-methylbutyric (P <0.05) decreased of concentration of isobutyric and isovaleric in rumen fluid than the other treatments. It is concluded that supplementation of branched chain volatile fatty acids not used by rumen bacteria for their growth but for the elongation of fatty acid synthesis. The supplementation of branched chain volatile fatty acids was 0.05 mM not enough strong influence on the growth of colony of rumen bacteria. (Animal Production 11(2): 129-134 (2009) Key Words: rumen fermentation, branched-chain fatty acid, ruminal bacteria, protozoa